The Influence Of Posyandu Service Quality On Patient Satisfaction At Kumbe Health Center, Bima City - Andang Sanjaya; Irma Mardian; Ismunandar (Journal AGENCY, 2025)
The aim of this research is to determine the influence of Posyandu Service Satisfaction on Patient Satisfaction at Kumbe Pueskesmas. The population in this study were all people who had received posyandu services. The type of research used in this research is associative. The data collection method uses a questionnaire. The data analysis technique used is simple regression analysis using statistical calculations through the statistical package application for social sciences (SPSS). The results of this research indicate that the Customer Satisfaction variable influences patient satisfaction at the Kumbe Community Health Center